Quality of service and continuous improvement at a national hospital Emergency Department’s Gynecology and Obstetrics’ topic - Acho Mego, Segundo (2015)
Objectives: To determine the quality of care and develop a continuous improvement of quality at the topic of Gynecology and Obstetrics of an emergency department. Design: Descriptive study. Setting: Hospital Nacional Cayetano Heredia Emergency department’s Obstetrics and Gynecology topic, Lima, Peru.  Participants: External users of the Obstetrics and Gynecology topic. Methodology: We determined the quality of care for external users; we designed a plan for continuous improvement of quality by the attitudinal problem of the doctor-patient relationship. We conducted a brainstorming session to build the Ishikawa diagram on "Attitude of staff that gives inadequate attention at the Gynecology and Obstetrics topic." A project for continuous quality improvement was developed. Main outcome measures: Quality of care and a continuous quality improvement project. Results: Of the 60 patients surveyed during 2008 at the hospital 84% said they had Integral Health Insurance, and they came to the hospital because there was good care (10%) and 6% because the hospital was near. Results were evaluated by the Pareto diagram: in 93% the staff did not welcome the users, in 80% the staff did not adequately explain de evaluation to be done, and in 77% there was no adequate information of the evaluation done to the patient by the staff. Results of the continued improvement plan held during July, August, and November 2008 were as follows. The objective to improve in 90% identification or oral presentation of the staff, proper attention was fulfilled respectively in 12 (40%), 6 (20%) 10 (50%). The goal to improve by 90% information on the clinical examination was obtained respectively in 21 (70%), 9 (30%) and 12 (60%). The goal to improve by 90% information on clinical test results was obtained respectively in 24 (80%), 12 (40%), 12 (60%). Conclusions: Continuous improvement activities promoting change of attitude of the internal user improved information provided to patients in a Gynecology and Obstetrics topic.